Mewujudkan Good Governance Melalui Tata Kelola Administrasi di Desa Sidoagung Kecamatan Tempuran Kabupaten Magelang - Tjatur Supriyono; Betricia Yohana; Windy Kartika Putri; Khairul Muslim (JURNAL NAGARA BHAKTI, 2026)
This Community Service Program (PKM) aimed to strengthen the implementation of good governance principles through the optimization of administrative governance in Sidoagung Village, Tempuran District, Magelang Regency. Village administrative governance serves as a fundamental instrument in establishing transparent, accountable, effective, efficient, and participatory village government, as mandated by Law Number 6 of 2014 on Villages and Minister of Home Affairs Regulation Number 47 of 2016 concerning Village Government Administration. The preliminary assessment identified several issues, including unsystematic archival management, manual and poorly documented correspondence recording, limited understanding of administrative standards among village officials, and the absence of standardized administrative service procedures (SOP). The program applied a participatory and collaborative approach consisting of preliminary observation, needs assessment, socialization of good governance principles, technical training on village administration, drafting of service SOPs, implementation mentoring, and comparative evaluation before and after the intervention. The activity involved 13 lecturers and 11 supporting personnel, with 348 participants comprising village officials, village institutional representatives, and community members involved in administrative services. The results demonstrated significant improvement in village officials’ conceptual understanding of transparency, accountability, effectiveness, efficiency, and public participation principles. Technically, improvements were observed in archival classification and organization, systematic recording of incoming and outgoing correspondence, better documentation of population administration, and the formulation of draft administrative service SOPs as a foundation for service standardization. Post-activity evaluation indicated enhanced public service quality characterized by more structured procedures, increased responsiveness, and greater transparency. Beyond technical improvements, the program also fostered positive changes in the work culture of village officials toward a more professional and service-oriented governance model. Therefore, this community service initiative provides a tangible and sustainable contribution to strengthening village administrative governance as a foundation for implementing good governance at the local government level. Keywords: good governance, village administrative governance, public service, capacity building, community service program.